Simplicity, equality, and slavery : an archaeology of Quakerism in the British Virgin Islands, 1740-1780 - Chenoweth, John M. (Florida Museum of Natural History: Ripley P. Bullen series, 2017)
The author uses archaeological and archival information to reveal the everyday life of this group of Quakers residing in the British Virgin Islands between 1741 and 1763. He traces this discreet group of mostly poor, white planters settled on Tortola in the community of Little Jost van Dyke from the earliest documented appearance in the 1740 records, through the final census--which showed only five enslaved inhabitants remaining in the community